(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
the article examines the features of the functioning of computer lexicography in the context of educational discourse in Uzbek and English. A comparative analysis of digital lexicographic resources, electronic dictionaries and corpus systems used in pedagogical practice is carried out. Special attention is paid to the discursive teaching strategies characteristic of both languages. The differences in the structure of educational interaction, the depth of lexicographic description and the degree of integration of digital technologies into the educational process are revealed. Based on the analysis, recommendations are proposed for improving Uzbek digital lexicography and modernizing educational discourse, taking into account international experience.